Photocatalytic methane conversion to high-value chemicals - Youxun Xu; Enqi Chen; Junwang Tang (Carbon Future)
Methane has a substantial and widespread reserve on Earth. As a very abundant carbon and hydrogen source, as well as an energy vector, upgrading methane to higher-value fuels and chemicals (carbon oxygenates, C2+ hydrocarbons, etc.) is a promising technology in the supply of energy and chemicals by a low-carbon process. Due to the stable and inert nature of methane, activating and converting the molecule is extremely challenging. Currently, commercial methane conversion technology operates at high temperatures and/or high pressure, suffering from intense energy consumption and high capital investment. Photocatalysis, using photons as the only energy input, can operate at mild temperatures and under atmospheric pressure, which is a promising and green technology for methane conversion to high-value products. In this review, fundamental understandings of photocatalytic methane conversion and product selectivity involving different oxidants are discussed. Then recent advances in photocatalysts for methane conversion to hydrocarbons and oxygenates are detailed, including the relevant reaction mechanism and reaction pathways. Finally, the challenges and perspectives for photocatalytic methane conversion will be discussed based on the current progress and fundamental understanding.